Mastering Unreal Engine 4.X. - A.Moniem, Muhammad (Packt Publishing, 2016)
Take your game development skills to the next level with one of the best engines on the marketAbout This Book Build an entire AAA game level throughout the book Take your C++ scripting skills to the next level and use them extensively to build the game An advanced practical guide with a tutorial style approach that will help you make the best of Unreal engine 4Who This Book Is ForThis book is for game developers who have a basic knowledge of Unreal Engine and C++ scripting knowledge. If you want to take the leap from a casual game developer to a full-fledged professional game developer with Unreal Engine 4, this is the book for you. What You Will Learn Script your player controls in C++ Build a superb and engaging level with advanced design techniques Program AI with C++ Use Cascade to add life to your games Use custom shaders and advanced shading techniques to make things pretty Implement an awesome UI in the game Control gameplay using data tablesIn DetailUnreal Engine 4 has garnered a lot of attention in the gaming world because of its new and improved graphics and rendering engine, the physics simulator, particle generator, and more. This book is the ideal guide to help you leverage all these features to create state-of-the-art games that capture the eye of your audience. Inside we'll explain advanced shaders and effects techniques and how you can implement them in your games. You'll create custom lighting effects, use the physics simulator to add that extra edge to your games, and create customized game environments that look visually stunning using the rendering technique. You'll find out how to use the new rendering engine efficiently, add amazing post-processing effects, and use data tables to create data-driven gameplay that is engaging and exciting. By the end of this book, you will be able to create professional games with stunning graphics using Unreal Engine 4!Style and approachAn advanced guide that will take you to the next level of developing games with Unreal engine with illustrative examples that will make you confident of creating customized professional level games on your won.